PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS BAHAN AJAR MIND MAPPING UNTUK MEMBANGUN KEMAMPUAN HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 9 KAB. MAROS - ., Usman; Amri, Muhammad; ., Haeril (Universitas Islam Negeri Alauddin Makassar, 2019)
This paper describes the implementation of Islamic Religious Education learning based on mind mapping teaching materials for students in SMA Negeri 9 Kab. Maros. The purpose of this study was to describe the impact of learning in the form of student learning outcomes through the application of mind mapping based Islamic teaching materials in SMA Negeri 9 Marusu, Kab. Maros.This type of research is an experiment or trial in Class XI MIPA 1 with 35 students. The trial was conducted 4 times. The research instrument used was an observation sheet and a test of learning outcomes. Data analysis technique is quantitative descriptive analysis by finding the mean and degree of improvement in learning outcomes. The results showed that all stages of the implementation of PAI learning based on mind mapping went well, and the learning outcomes of students after using mind mapping PAI based learning materials increased by 27.51 from the pre-test mean value of 54.94 to the post-test average value 82.45.